KONFLIK DAN INTEGRASI DALAM MASYARAKAT PLURAL: JAMBI 1970-2012 - Lindayanti, Lindayanti; Zaiyardam, Zaiyardam (Paramita: Historical Studies Journal, 2015)
Jambi region was constituted by plural society. The social relations formed within a long period had created a conducive environment for plural society. The citizens were used to deal with people from different social and cultural background, and the differences of social class, religion, group and culture did not trigger conflict. Furthermore, interactions among ethnics, i. e. Melayu, Jambi, Minangkabau, Banjar, Bugis, Java and Batak even gave birth to new identity; the Jambi society. Nonetheless, the infiltration of big capital owners and trans-migration in 1990s had shaken this stability. The climax took place during the reformasi when a huge number of unrests surfaced, where society demanded the return of the land to the hands of people. It was important to build and employ attempts to lessen the tense and conflicts in this plural society. The local wisdom of Jambi people which has been formed for decades needed to be returned as a foundation for this attempt. Before capitalism dominated the life of the society, the values of local wisdom were proven to keep the plural society in harmony.Â Wilayah Jambi dihuni oleh masyarakat yang plural. Relasi sosial yang terjadi terbentuk dalam kurun waktu yang lama dan telah membentuk lingkungan yang kondusif untuk masyarakat plural. Penduduknya telah memiliki kesepahaman terhadap masyarakat dengan latar sosial dan budaya yang berbeda, dan perbedaan kelas, agama, kelompok, serta budaya tidak memicu terjadinya konflik. Lebih lanjut lagi, interaksi antara etnik Melayu, Jambi, Minangkabau, Banjar, Bugis, Jawa, dan Batak bahkan melahirkan identitas baru sebagai masyarakat Jambi. Akan tetapi, infiltrasi dari para pemodal besar dan transmigrasi pada tahun 1990-an telah mengguncang stabilitas yang ada. Puncaknya terjadi selama reformasi ketika sejumlah besar kerusuhan muncul, di mana masyarakat menuntut pengembalian tanah. Untuk itu, penelitian ini penting dilakukan untuk mengurangi ketegangan dan konflik dalam masyarakat. Kearifan lokal masyarakat Jambi yang telah dibentuk selama puluhan tahun perlu dikembalikan sebagai dasar untuk upaya ini. Sebelum kapitalisme mendominasi kehidupan masyarakat, nilai-nilai kearifan lokal yang terbukti untuk menjaga masyarakat plural dalam harmoni.Â